2017
DOI: 10.3389/fpls.2017.01766
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic and Salt Stresses Modulate Spontaneous and Glutamate-Induced Action Potentials and Distinguish between Growth and Circumnutation in Helianthus annuus Seedlings

Abstract: Action potentials (APs), i.e., long-distance electrical signals, and circumnutations (CN), i.e., endogenous plant organ movements, are shaped by ion fluxes and content in excitable and motor tissues. The appearance of APs and CN as well as growth parameters in seedlings and 3-week old plants of Helianthus annuus treated with osmotic and salt stress (0–500 mOsm) were studied. Time-lapse photography and extracellular measurements of electrical potential changes were performed. The hypocotyl length was strongly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…The endogenous excessive accumulation of the glutamate under normal or stressed conditions or through its exogenous application, confirms its role as a signaling molecule in ameliorating the deleterious effects of multiple abiotic stresses [31]. For example, the exogenous application of glutamate on Brassica compestris reduced the negative impacts of salt and osmotic stress [33]. Ramos et al [34] reported an endogenous increase in glutamate of Glycine max L. grown under water deficiency, resulting in the increased accumulation of many other amino acids along with its own accumulation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The endogenous excessive accumulation of the glutamate under normal or stressed conditions or through its exogenous application, confirms its role as a signaling molecule in ameliorating the deleterious effects of multiple abiotic stresses [31]. For example, the exogenous application of glutamate on Brassica compestris reduced the negative impacts of salt and osmotic stress [33]. Ramos et al [34] reported an endogenous increase in glutamate of Glycine max L. grown under water deficiency, resulting in the increased accumulation of many other amino acids along with its own accumulation.…”
Section: Introductionmentioning
confidence: 84%
“…It might be the fact that glutamate might also have played an additional role in improving the water stress tolerance of ajwain plants [35]. It has been found earlier that foliar-supplied glutamate was found helpful in enhancing plant performance and alleviating the harmful effects of stress in faba bean and Brassica napus plants [33,35], respectively. In rice, Jie et al [67] reported that amino acidchelated Zn and Fe better improved the yield as compared with respective chemical fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the role of Cl − in the regulation of water transport and cell volume in plants, Cl − fluxes are specifically required for the proper functioning of specialized motor cells like the pulvini of leguminous plants during seismonastic and nystinastic leaf movements [39,40,41], and guard cells during stomatal opening and closure [42,43]. Osmotically-driven water fluxes are also essential for endogenous plant organ movement or circumnutation [44]. While transmembrane ionic fluxes necessarily involve electroneutral transport with K + , the activation of PM anion channels is often the triggering element that connects environmental cues with the response of the corresponding motor cell, as observed in the stomatal closure or the circadian-regulated leaf opening [45,46].…”
Section: Cl− As a Beneficial Macronutrientmentioning
confidence: 99%
“…In response to Ca(NO 3 ) 2 , the mitochondrial numbers and structure of the two cultivars of cucumber showed great changes. This result could be explained through the osmotic stress effects of plant root growth [24]. Previous work showed that salt stress conditions had a suppression role in the growth of plants [25].…”
Section: Discussionmentioning
confidence: 93%